Pengaruh Variasi Polivinilpirolidon (PVP) Terhadap Pembentukan Serat Nano TiO2 Menggunakan Metode Electrospinning - Vega Rahmawati Ar; Posman Manurung; Junaidi Junaidi; Pulung Karo Karo (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Research on the formation of TiO2 nanofiber has been carried out with PVP variations of 1.1; 1,2; 1.3; 1.4 and 1.5 grams using electrospinning. This study aims to determine the effect of PVP variation on the viscosity and morphology of TiO2 nanofibers and to determine the crystal structure of the fibers. Synthesis of TiO2 was carried out using the sol-gel method. TTIP is used as a precursor, ethanol as a solvent, acetic acid as a catalyst and PVP as a fiber-forming polymer. The results of the viscosity measurement show that the amount of PVP used in the sample is directly proportional to the level of solution viscosity. Based on the results of SEM characterization, it showed relatively uniform nanofiber morphology with fiber diameter ranging from 94 nm - 735 µm. The results of TEM characterization showed that the size of TiO2 nanofiber particles ranged from 7-15 nm. The results of XRD analysis showed that the crystal structures formed at a calcination temperature of 450 oC were the anatase and rutile phases.